The ideology of Republican propaganda in Parahyba do Norte, through the pages of the newspaper "Verdade" from the city of Areia, PB (1888-1892). - de Queiroz, Ivandro Batista (2023)
This article aims to analyze the main ideological influences in the Republican campaign and the early years of the establishment of the republican institution in Brazil. The space occupied in the propaganda by ideologies other than the most famous one (positivism), such as American liberalism and French Jacobinism, appealed for political participation in the new regime, expressed through frequently repeated words like freedom and democracy. The establishment of the Republic became synonymous with democracy, freedom, and progress, while the Monarchy became synonymous with archaic, backwardness, and authoritarianism. In the end, an oligarchic Republic was installed, leading to dissatisfaction with the political direction the country took.